Proyeksi Kenaikan Muka Air Laut dan Dampaknya berdasarkan skenario Shared Socioeconomic Pathways di Pulau Enggano tahun 2020-2150 - Iwan Pramesti Anwar; An Nisa Nurul Suci; Mukti Dono Wilopo; Aulia Try Atmojo; Faruq Khadami (Universitas Bengkulu, 2025)
Global climate change is causing significant impacts across various regions of the world, one of which is the rise in sea level in Pulau Enggano. Utilizing The NASA Sea Level Projection Tool and The Coastal Risk Screening Tools, this research successfully analyzes the projections of sea level rise and coastal inundation areas in Pulau Enggano. Seven Shared Socioeconomic Pathways (SSP) scenarios for the years 2050, 2100, and 2150 are analyzed. The analysis results indicate significant risks: by 2050, the rise in sea level is expected to range from 0.05 m to 0.2 m, with inundated areas remaining limited, primarily affecting a small part of the Tanjung Laksaha nature reserve. The average rate of sea level increase during this period varies between 4 mm/year and 12 mm/year. In 2100, projections show that the inundated areas will expand, with optimistic scenarios like SSP1-1.9 estimating a rise of about 0.4 m, while pessimistic scenarios such as SSP5-8.5 could reach 0.89 m. This sea level rise indicates an increased risk of damage to infrastructure. Meanwhile, by 2150, nearly the entire northern and eastern coast of the island is expected to be submerged, with optimistic scenarios showing lower increases compared to pessimistic scenarios, which could exceed 2.5 m. These findings underscore the urgent need for adaptation and mitigation strategies to ensure the sustainability of Pulau Enggano in the future. Keywords: Sea level rise, Climate Change, inundation map, Enggano Island